Infection Prevention Strategies in Cardiac Rehabilitation: A Behavioral Intervention for Patients and Contemporary Applications - Bjerke, Wendy (Disease and Health: Research Developments Vol. 4, 2025)
Background: Annually in the United States, it is estimated that 1.7 million patients acquire a healthcare-associated infection (HAI), defined as an infection acquired in a hospital or healthcare facility which results in approximately one hundred thousand deaths. Healthcare Acquired Infections (HAI) result in over 100 thousand deaths each year with one-third of these deaths preventable via behaviors such as hand washing among healthcare providers in inpatient settings. Less research has been conducted in outpatient exercise settings such as cardiac rehabilitation (CR) among patients. Purpose: The purpose of this study was to examine the effectiveness of HAI prevention strategies in a CR setting among patients. Methods: Observations of the frequency of hand washing among CR patients pre and post-four HAI strategies including provision of HAI education and signs, hand washing demonstrations, an HAI prevention video, and hand sanitizer samples. Washing hands prior to CR (WI) was observed as well as washing hands prior to leaving the CR center (WO). Methods included recording the frequency of WI and WO among all patients at baseline and after each of the four interventions. Mean frequencies of WI and WO were compared among a mean of 22 - 43 CR patient visits over 12 weeks using descriptive statistics and t-tests to determine if changes were significant pre and post-intervention strategies. Results: At baseline, no patients WI or WO during an outpatient CR visit. Post interventions 1 - 4, the percentage of patients WI and WO was 33 and 34, 32 and 26, 32 and 29, 33 and 22 respectively. At a one-year follow up, the percentage of patients WI and WO was 40%. Conclusion: Increases in frequency and the percentage of WI and WO were observed among patients meriting continued examination of HAI prevention strategies among patients in outpatient exercise settings such as CR. Given that the provision of feedback is suggested, the examination of HAI infection strategies outcomes in this study could benefit the patients and staff of CR centers and be applied to other rehabilitation settings such as physical therapy, occupational therapy, and therapeutic fitness centers.